Gambaran Karakteristik dan Beban Kerja pada Pekerja Bagian Produksi Suku Cadang Otomotif PT. “X” Cikarang - Nada Nabila Ramadhani; Titik Respati; Purnomo (UNISBA Press, 2024)
Abstract. Musculoskeletal disorders are a primary work-related health concern globally, often leading to disability and lost work years. This study explores the distribution of characteristics and workloads among workers in automotive production at PT.